Aspect, Aktionsart, and Abduction: Future Tense in the New Testament - Pang, Francis G. H. (Filología neotestamentaria, 2010)
This study examines the treatment of the Future tense among the major contributions in the discussion of verbal aspect in the Greek of the New Testament. It provides a brief comparative summary of the major works in the past fifty years, focusing on the distinction between aspect and Aktionsart on the one hand, and the kind of logical reasoning used by each proposal on the other. It shows that the neutrality of the method is best expressed in an abductive approach and points out the need of clarifying the nature and the role of Aktionsart in aspect studies.